PENURUNAN BIAYA RANSUM BERBASIS LIMBAH TEBU DENGAN PEMANFAATAN Thitonia diversifolia UNTUK SAPI BALI - Adrizal, Adrizal (Pastura, 2017)
The research is aimed to minimizing the diet costs of bali beef cattle by using sugarcane waste as an energy source and Thitonia diversifolia as a source of protein. Diet formulated using linear programming (LP) with QSB+ software. The input data was the price, nutrient content and limitation of the feed stuffs used, as well as nutritional requirements of bali cattle. The output of the LP was composition and price of diet. Research conducted at the center for the production of sugar cane in Kenagarian Talang Babungo, Hiliran Gumanti District, Solok Regency, Sumatera Barat Province. The feed stuffs that are potential is provided on site research was sugar cane top, bagasse, liquid waste processing of sugar cane, rice bran, palm kernel cake, Thitonia diversifolia, minerals and salts. The treatment was the level of use Thitonia diversifolia in rations which is 0%, 7.5%, 15% and 22.5%. Diet formulation results showed decreased amounts of usage for palm kernel cake of the using Thitonia diversifolia. The decrease of using palm kernel cake caused minimizing of complete diet cost. The price of the diet (dry matter basis) without Thitonia diversifolia was Rp. 1481/kg, whereas the use of as much as 7.5%, 15% and 22.5% caused the price of ration Rp. 1354/kg, Rp. 1296/kg to and Rp. 1239/kg respectively. The conclusion was the use of Thitonia diversifolia can minimize thecost of diet for bali beef cattle in the site of research. Keywords: sugar cane waste, Thitonia diversifolia, diet cost, linear programming, Bali cattle.